Airlangga : biografi raja pembaru Jawa abad XI - Susanti, Ninie, 1956- (Depok : Komunitas Bambu, 2010)
Account of Airlangga, King of Kahuripan Kingdom.
Includes bibliographical references (p. 245-262) and index.
Keywords: Java (Indonesia) -- History; Indonesia -- History -- To 1478